2017
DOI: 10.1017/age.2016.37
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Switching Production Options in a Flexible Biorefinery

Abstract: This study analyses the value of a switching option in a flexible biorefinery plant that produces ethanol and sugar juice in a single plant using energy beets. A real-options approach is used to compute threshold prices and optimal switching decision rules for switching between sugar and ethanol production modes. The analysis shows that it is economically optimal to keep producing ethanol then switching to sugar juice, given the stochastic price parameters of the two products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In chemical engineering, one of the most common uses of flexibility is as a component of operability, this is often named operational flexibility ,,,− or process flexibility . , Flexibility is usually defined as the ready capability of a plant to operate over a range of conditions feasibly . Walsh and Perkins considered operability as the ability of a system to tackle uncertainty, accommodate disturbances, and resolve concerns for reliability and maintenance.…”
Section: State-of-the-artmentioning
confidence: 99%
“…In chemical engineering, one of the most common uses of flexibility is as a component of operability, this is often named operational flexibility ,,,− or process flexibility . , Flexibility is usually defined as the ready capability of a plant to operate over a range of conditions feasibly . Walsh and Perkins considered operability as the ability of a system to tackle uncertainty, accommodate disturbances, and resolve concerns for reliability and maintenance.…”
Section: State-of-the-artmentioning
confidence: 99%
“…RCF's initial investment cost of 123 M€ (Tschulkow et al, 2020) Hossiso and Ripplinger (2017). Lignin-derived products (monomers and oligomers) have a broad range of applications, e.g.…”
Section: Scenario 1: Separated Investments In Harvesting Equipment An...mentioning
confidence: 99%
“…Several real options studies were conducted on biorefineries but only a few are applicable to woodbased biorefineries. For instance, Brambila-Paz et al (2013) and Hossiso and Ripplinger (2017) concluded that the flexible option to switch production is an added value to the evaluation. However, their focus is on first-generation biomass such as sugarcane and energy beets respectively, and not wood.…”
Section: Introductionmentioning
confidence: 99%
“…If agility is now a well known topic in the manufacturing industry (especially within the frame of Industry 4.0), it is surprisingly pioneering in the chemical process industry [8].…”
Section: Introductionmentioning
confidence: 99%